Liver function parameters aspartate aminotransferase and total protein predict functional outcome in stroke patients with non-cardioembolism - Xie, Jiali; Zhu, Yinmeng; Pang, Chunyang; Gao, Lingfei; Yu, Huan; Lv, Wenjing; Zhang, Wanli; Deng, Binbin (Frontiers in Nutrition, 2022)
Stroke, classified as cardioembolism and non-cardioembolism (non-CE), entails a large socioeconomic burden to the elderly. The morbidity and mortality of non-CE are high, whereas studies concerning prognostic factors impacting function outcome remain underdeveloped and understudied. Liver function parameters are convenient approaches to predicting prognosis in cardiovascular diseases, but their clinical significance has not been well-characterized in stroke, especially in non-CE. In our study, a total of 576 non-CE patients at 1 year of follow up were enrolled in a cohort from a consecutive hospital-based stroke registry, with randomly 387 patients as development cohort and 189 patients as validation cohort. Univariate and multivariate analysis revealed the following novel findings: (i) The incidence of unfavorable functional outcome after non-CE was significantly greater (p<0.01) in patients with higher age, aspartate amino transferase (AST), National Institutes of Health Stroke Scale (NIHSS) score and depressed total protein (TP). (ii) We established a novel model and nomogram to predict stroke prognosis, in addition to the known factors (age and NIHSS score). The levels of AST and TP were independently correlated with the incidence of unfavorable outcome (AST: OR = 1.026, 95% CI (1.002-1.050); TP: OR = 0.944, 95% CI (0.899-0.991)). (iii) The results persisted in further subgroup analysis stratified by age, gender, NIHSS score and other pre-specified factors, especially in males 60 years or older. Overall, this study demonstrates that hepatic parameters (AST and TP) after non-CE are considered to be associated with functional outcome at 1-year follow-up, especially in males aged ≥60 years.